The metamorphosis of the giant Nicteroy in Brazilian conservatism since 1822 = Metamorfoza olbrzyma Nicteroya w brazylijskim konserwatyzmie od 1822 roku - Alvarez, Beethoven (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In 1821-1822, Pedro I, then Prince Regent of Brazil, faced a crisis that culminated in the proclamation of independence on September 7, 1822. During this period, Januário da Cunha Barbosa (1780-1846) published the poem "Nicteroy: Metamorphose do Rio de Janeiro" (1822). The poem could be described as an Indianist epic poem, based on the topos of metamorphosis and on an ancient mythical background that included Claudianus`s "Gigantomachia".
Keywords: classical reception studies; "Gigantomachia"; metamorphosis; Brazilian literature; Brazilian conservatism; metamorfoza; literatura brazylijska; konserwatyzm brazylijski